"Natural" Claims in Food Advertising: Policy Implications of Filling the Regulatory Void with Consumer Class Action Lawsuits. (April 2015) - Petty, Ross D.
Many consumers find advertising and labeling claims that a food is natural to be both compelling and trustworthy. For this reason, both the Federal Trade Commission and the Food and Drug Administration have long considered taking regulatory action to define "natural" in the food advertising context to prevent deception. However, neither agency has taken definitive action. As a result, consumer class action attorneys have seized this opportunity of regulatory inaction to file numerous lawsuits against food marketers that advertise their products as natural. Unfortunately, the litigation to date has predominantly involved procedural issues such as class certification rather than policy issues regarding an appropriate definition of "natural" for food advertising. The piecemeal approach of litigation is unlikely to result in a consistent, well-reasoned definition of "natural" for the benefit of food advertisers and consumers alike. However, the litigation does demonstrate continued interest in this issue, and perhaps this interest will cause regulatory agencies to reconsider providing better guidance, if not formal regulation.